Socialization of Good Communication Strategies in Creating Good Service Quality on Campus: Pengabdian - Kushariyadi, Kushariyadi; Dewi, Erlita Khrisinta; Masduki, Damayanti; Manuhuruk, Hermina; Widianingsih, Yuliani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The author conducted outreach activities over a seven-day period at several campuses, including the Akamigas Energy and Mineral Polytechnic, the APP Jakarta Polytechnic, and the Veteran National Development University. The author expresses his deepest gratitude to all parties involved, from the outreach activities to the publication of this article. He especially extends his thanks to his supervisor, fellow lecturers, friends who participated in the outreach activities, educators, students, and others. He hopes we can communicate effectively and achieve our vision and mission.